Structural Characterization and Drug Delivery System of Natural Growth-Modulating Peptide Against Glioblastoma Cancer - Budama-Kılınç, Yasemin; Keçel-Gündüz, Serda; Çakır-Koç, Rabia; Aslan, Bahar; Bıçak, Bilge; Kökçü, Yağmur; Özel, Ayşen E.; AKYÜZ, SEVİM (Springer, 2021)
The aim of the current study was to design a drug delivery nano-system of natural growth-modulating peptide known as GHK that naturally occurs in human plasma, saliva, and urine and determine possible anticancer activity against glioblastoma cancer based on in-silico and in-vitro evaluations. In this current study, a drug delivery nano-system based on Poly(epsilon-caprolactone) (PCL) were prepared by a double emission-precipitation method with different preparation parameters for optimization. The characterization of the optimum nanoparticles was performed with Zeta-Sizer, Ultraviolet-Visible (UV-Vis), Fourier Transform Infrared spectroscopy (FT-IR) and Raman spectroscopy, and Transmission Electron Microscopy (TEM) methods. The optimum size of the GHK loaded PCL nanoparticle was prepared with a 232.5 +/- 0.72 nm average particle size, - 10.8 +/- 0.64 mV zeta potential, and a 0.029 polydispersity index, 82.3% of encapsulation efficiency and 73% of loaded efficiency. In vitro cytotoxicity test revealed that the GHK loaded PCL nanoparticles had anticancer effect on glioblastoma cells. In vitro release study showed the sustained release behavior of GHK from nanoparticles during the period of 10 days study. In addition, molecular dynamics and molecular docking calculations, in vitro release study, and cytotoxicity tests showed that GHK loaded PCL nanoparticles may be used effectively for glioblastoma cancer therapy.
Keywords: Tripeptide; Poly(ε-caprolactone); Nanoparticle; Molecular Docking; Computational Design